PERANCANGAN APLIKASI E-INFORMATION DAN JADWAL PERKULIAHAN BERBASIS MOBILE ANDROID - Abdul Rahim (Jurnal PROCESSOR, 2017)
In this research, the development of e-information system on STIKOM Dinamika Bangsa Jambi. The e-information system is used by STIKOM Dinamika Bangsa to provide course timetable information and other latest information to students. In the implementation, students still have to go to campus STIKOM to see the attendance schedule of lecturers. And the lecturer should inform the cancellation of the college schedule to the academic section. In this study, the authors do the development of android mobile applications that can be used by lecturers to cancel cancellation schedule, and in the process of cancellation will send notification to the students so that students receive the lecture schedule information more quickly. The design of this application using the material design and the way this application is, the android e-information application performs an encrypted request to the API (application programming interface) database e-information stikom. After going through the authentication process, then through the API data base e-information stikom provide appropriate response to the demand for android-based e-information applications. This application requires internet connection and data sent in using this application <30kbps in each request process. Based on testing, this application can run well featuring lecture schedules, campus information and notifications in the event of cancellation of college schedule.